2021
DOI: 10.3892/etm.2021.10199
|View full text |Cite
|
Sign up to set email alerts
|

Association of oral Epstein‑Barr virus with periodontal health in Japanese adults

Abstract: Previous studies have demonstrated that oral Epstein-Barr virus (EBV) is associated with periodontitis. However, the relationship between periodontitis and oral EBV has not been fully elucidated by reducing the effects of confounding factors. The aim of the present study was to clarify the association between oral Epstein-Barr virus (EBV) and oral health status among middle-aged and older Japanese individuals. A total of 124 patients (46 males and 78 females; mean age, 69.2 years; age range, 35-90 years) who v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Several studies have demonstrated an association between oral health and EBV infection, as well as a strong association of EBV with periodontitis [ 56 ]. Inflamed periodontal pockets may be a reservoir for the EBV virus, which will then infect oral epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an association between oral health and EBV infection, as well as a strong association of EBV with periodontitis [ 56 ]. Inflamed periodontal pockets may be a reservoir for the EBV virus, which will then infect oral epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is controversial whether HHV-7 is closely associated with periodontitis. We had previously found that EBV and CMV were significantly associated with the presence of a deep periodontal pocket with bleeding [ 3 , 23 ]. Therefore, oral herpesviruses such as EBV and HCMV, rather than HHV-7, may be more closely associated with active periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…[5] We previously reported that patients with deep periodontal pockets with bleeding exhibited a greater oral EBV DNA positivity rate than did those without deep periodontal pockets with bleeding, indicating a significant relationship between oral EBV infection and periodontitis. [6] These results suggest that oral EBV is importantly involved in the etiology of periodontitis. Furthermore, interaction between EBV and periodontitis-related bacteria may contribute to periodontitis development and progression.…”
Section: Introductionmentioning
confidence: 93%
“…[12] A 180-bp DNA fragment of the EBV genome cloned into a pUC57 vector was obtained from GenScript Biotech Corporation (Piscataway, NJ). [6] Standard curves for 10-fold serial dilutions of the EBV genome inserted into a pUC57 vector (1.55 × 10 7 -1.55 × 10 2 copy/μL) were used to determine EBV-positive samples (Fig. S2, http://links.lww.com/MD/H707).…”
Section: Detecting Ebv Dna and P Gingivalis By Real-time Pcrmentioning
confidence: 99%